NILAI PENDIDIKAN DALAM AL-QUR’AN - Nursyamsu Nursyamsu (LP2M STAI Darul Kamal NW Lombok Timur, 2016)
The Qur'an in it contained many educational values that can be picked from a paragraph to paragraph in the letter and juz. The value of education in the Qur'an or being able to adapt with the times. The value of an education in the Qur'an that is stories of the prophets and giving examples such as the Prophet Ibrahim, Ismail and the Lukmanul Hakim recounted in the Quran Luqman verse 13 and ash-Shaffat verse 102. The interpretation of the verses is the content of the educational values, all values that can be obtained through science, the science of education.